(untitled) (African Journal of Biomedical Research, 2020)
In scholarly publication, authorship defines the roles played by an individual or a member of a team in creating and circulating an original work. It is therefore important to clearly understand who deserves to be an author in a publication. Also, the order or position of authors in a scholarly publication often leads to conflict among members of research teams. This is not helped by the advent of more technical reward systems for promotion, tenure and grants in many institutions, some of which give advantage to the position of some authors. In this paper, some common issues on authorship and peer review processes are discussed.